If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 87 = a + 48 Reorder the terms: 87 = 48 + a Solving 87 = 48 + a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. 87 + -1a = 48 + a + -1a Combine like terms: a + -1a = 0 87 + -1a = 48 + 0 87 + -1a = 48 Add '-87' to each side of the equation. 87 + -87 + -1a = 48 + -87 Combine like terms: 87 + -87 = 0 0 + -1a = 48 + -87 -1a = 48 + -87 Combine like terms: 48 + -87 = -39 -1a = -39 Divide each side by '-1'. a = 39 Simplifying a = 39
| f+6=87 | | -5(-9z+1)=2(8+7z) | | 54=82-y | | 25-b=15 | | c+15=76 | | c+15=76 | | x=18+2x | | 4=s/9 | | 57-t=49 | | (x+2)/3-4x=8 | | y^2-13y+36/3y-12 | | x+3-4x=0 | | 12y=6-2x | | 3(x)=1/2x+5 | | 9+v=36 | | 7k-21=3k-5 | | 17=p-5 | | 31=3+m | | k+36=40 | | 9x^4+12x^2+4= | | 65-h=54 | | x-51=27 | | 54=6z | | 14=7r | | 8x+33=5x+87 | | 60y^2-51y-72=0 | | 3x^2-9x=30 | | d-(-4)=25 | | (2x+7)(x-8)=0 | | 3x^2+17x-12=0 | | 9g-6=3(4g+5) | | 3x^2-1/27x^6=0 |